Why Intelligence Fails : Lessons from the Iranian Revolution and the Iraq War - Jervis, Robert, 1940-2021 (Book collections on Project MUSE., 2010)
The U.S. government spends enormous resources each year on the gathering and analysis of intelligence, yet the history of American foreign policy is littered with missteps and misunderstandings that have resulted from intelligence failures. In Why Intelligence Fails, Robert Jervis examines the politics and psychology of two of the more spectacular intelligence failures in recent memory: the mistaken belief that the regime of the Shah in Iran was secure and stable in 1978, and the claim that Iraq had active WMD programs in 2002. The Iran case is based on a recently declassified report Jervis was commissioned to undertake by CIA thirty years ago and includes memoranda written by CIA officials in response to Jervis's findings. The Iraq case, also grounded in a review of the intelligence community's performance, is based on close readings of both classified and declassified documents, though Jervis's conclusions are entirely supported by evidence that has been declassified. In both cases, Jervis finds not only that intelligence was badly flawed but also that later explanations--analysts were bowing to political pressure and telling the White House what it wanted to hear or were willfully blind--were also incorrect. Proponents of these explanations claimed that initial errors were compounded by groupthink, lack of coordination within the government, and failure to share information. Policy prescriptions, including the recent establishment of a Director of National Intelligence, were supposed to remedy the situation. In Jervis's estimation, neither the explanations nor the prescriptions are adequate. The inferences that intelligence drew were actually quite plausible given the information available. Errors arose, he concludes, from insufficient attention to the ways in which information should be gathered and interpreted, a lack of self-awareness about the factors that led to the judgments, and an organizational culture that failed to probe for weaknesses and explore alternatives. Evaluating the inherent tensions between the methods and aims of intelligence personnel and policymakers from a unique insider's perspective, Jervis forcefully criticizes recent proposals for improving the performance of the intelligence community and discusses ways in which future analysis can be improved.